1984
DOI: 10.1049/ip-a-1.1984.0037
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic emission: its techniques and applications

Abstract: Acoustic emission offers the possibility of inspecting the whole volume of large structures from a limited number of access points. The paper discusses the historical development of the technique and describes the instrumentation and analytical methods used for interpretation. Experience has shown that, contrary to early statements, acoustic emission is not a universal inspection tool and the latter portion of the paper describes applications where the technique does have some chance of success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…This is consistent with the transmission electron microscopy observation in 304 stainless steel showing clear formation of carbides and their morphology on the grain boundaries. 4042 The severity of Cr carbide precipitation at grain boundaries is more in case of 24 h aged sample than the other specimen. Hence, it can be observed that the extent of carbide precipitation increases with increasing severity of sensitisation.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the transmission electron microscopy observation in 304 stainless steel showing clear formation of carbides and their morphology on the grain boundaries. 4042 The severity of Cr carbide precipitation at grain boundaries is more in case of 24 h aged sample than the other specimen. Hence, it can be observed that the extent of carbide precipitation increases with increasing severity of sensitisation.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 8a illustrates three distinct UHF sensors that are suitable for the purpose of PD detection on both power transformers and gas-insulated switchgear. Conventionally, the three types of sensors utilized for PD detection, according to reference [110], are disc-type, monopole-type, and spiral-type sensors. Recent research has revealed that these sensors accumulate a significant amount of energy, demonstrating their excellent sensitivity in detecting emitted signals [110].…”
Section: Combinational Methodsmentioning
confidence: 99%
“…Conventionally, the three types of sensors utilized for PD detection, according to reference [110], are disc-type, monopole-type, and spiral-type sensors. Recent research has revealed that these sensors accumulate a significant amount of energy, demonstrating their excellent sensitivity in detecting emitted signals [110]. Meanwhile, Figure 8b depicts a capacitive coupler used in a high-voltage cable for PD detection.…”
Section: Combinational Methodsmentioning
confidence: 99%
“…They are the disc-type, monopole-type, and spiral-type. The disc-type, monopole-type, and spiral-type sensors can provides the greatest energy accumulation in the laboratory test, which indicates that the sensors have the high sensitivity for detecting radiated signals [20]. Figure 3 shows a capacitive coupler for partial discharge detection in (a) (b) (c) Fig.…”
Section: Sensors For Electrical Quantity Measurementmentioning
confidence: 99%